ANALISIS KELAYAKAN KEUANGAN PEMBANGUNAN PABRIK BIODIESEL Studi Kasuspada PT ABC - , Novan Yahya Anandaputra, Dr. Erni Ekawati, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Renewable industry, especially biodiesel industry, has been growing rapidly. This is true either in the context of the prospect of renewable energy in domestic market or increasing demand of Indonesian biodiesel in foreign market. PT. ABC captures this opportunity by offering 20 Metric Ton per Day biodiesel plant to its customers. PT. ABCâs biodiesel plant will need an initial investment that a huge portion of this initial investment will be allocated in production machines and equipments. PT. ABC whose main business is in chemical engineering field will provide its customers all the machines and technical knowledge needed to operate this biodiesel plant. Before the investor agreed the proposal, investors need to perform a set of financial feasibility analysis in order to have information whether this project will increase their wealth or this project will reduce their fortune. Financial feasibility analysis shows that this project should be accepted. However, this project is judged to have enormous risk. Investor who decided to run this project should have risk management practice, such as hedging, in place in order to protect the return that is provided by this project.